Exploring the link between sustainable practices and corporate performance across industries - Iris Maria Velez Osorio (Business Systems Research (BSR), 2024)
Background The adoption of the Sustainable Development Goals (SDGs) has set a global standard for promoting sustainable practices. However, manufacturing companies need help in adopting these practices due to differences between industries, the need for research and development, and variations in corporate sizes. Objectives This analysis aims to study sustainability practices and their impact on corporate performance across different industries. It seeks to identify whether there is a relationship between sustainability practices and corporate performance in manufacturing companies and if the type of industry affects this relationship. Methods/Approach To achieve this goal, a multivariate analysis was conducted using hierarchical regression. Results The research indicates a direct connection between sustainability practices and corporate performance. It highlights the importance of creating distinctive sustainability practices that cater to the specific needs and characteristics of each industry. Conclusions Developing corporate strategies around sustainability is imperative. Additionally, public policies should be implemented to encourage the adoption of such practices, reinforcing the need for industry-specific approaches to enhance both sustainability and corporate performance.
Keywords: Q01; L6; 330; performance; sustainability; industry; manufacturing